2021
DOI: 10.1021/acs.nanolett.1c03427
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Receptor Membrane-Coating Facet Structures Boost Nanomaterial Immune Escape and Antibacterial Performance

Abstract: Nanomaterials show great potential for the treatment of bacterial infections, but their effects remain limited by low antibacterial efficiency and immune clearance. Facet-dependent nanozymes coated with pathogen receptor membranes were fabricated, providing an approach for producing superphotothermal antibacterial nanomaterials with high biocompatibility and low immune clearance. (100)- and (112)-Faceted CuFeSe2 presented excellent photothermal conversion efficiency (46%). However, the peroxidase-like activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Briefly, Si-Pc (27.8 mg, 45 µmol), PEG (100 mg, 50 µmol), and NaH (5 mg) were refluxed in anhydrous toluene (40 mL) under an argon atmosphere for 24 h. After rotary evaporation of toluene, the residue was dispersed in methanol and the filtrate was concentrated under reduced pressure to collect HO-PEG-Pc. 1 H NMR spectra were recorded on a Bruker AM 400 apparatus, using tetramethylsilane (TMS) as the internal reference. Yield: 47%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, Si-Pc (27.8 mg, 45 µmol), PEG (100 mg, 50 µmol), and NaH (5 mg) were refluxed in anhydrous toluene (40 mL) under an argon atmosphere for 24 h. After rotary evaporation of toluene, the residue was dispersed in methanol and the filtrate was concentrated under reduced pressure to collect HO-PEG-Pc. 1 H NMR spectra were recorded on a Bruker AM 400 apparatus, using tetramethylsilane (TMS) as the internal reference. Yield: 47%.…”
Section: Methodsmentioning
confidence: 99%
“…Yield: 62%. 1 H NMR (CDCl 3 ): δ 3.44-3.69 (CH 2 CH 2 O), 3.71 (OSiCH 2 CH 2 ), 3.81 (OCH 2 COOH), 8.32, and 9.61 (Si-Pc proton) (Figure 1e).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to further improve the ability of CMCNPs to target bacteria, the researchers stimulated the activation of PAMPs on macrophage membrane with pathogenic bacteria, which were then coated onto AuNPs, and they found that this system could better target bacteria (X. Hou et al, 2021;Wang et al, 2018).…”
Section: Targeting Bacteriamentioning
confidence: 99%